Motor units in incomplete spinal cord injury: electrical activity, contractile properties and the effects of biofeedback. - Stein, R B (1990)
The electrical and contractile properties of hand muscles in a selected population of quadriplegic subjects were studied intensively before and after EMG biofeedback. Spontaneously active motor units and units that could only be slowly and weakly activated were observed in these subjects, in addition to units that were voluntarily activated normally. This suggests a considerable overlap of surviving motor neurons to a single muscle that are below, near or above the level of a lesion. Despite the common occurrence of polyphasic potentials and other signs of neuromuscular reinnervation, the average twitch tension of single motor units in hand muscles of quadriplegic subjects was not significantly different from that in control subjects. Nor did it increase after biofeedback training that typically increased the peak surface EMG by a factor of 2-5 times. The percentage of spontaneously active units was also constant. The surface EMG may be increased during biofeedback by using higher firing rates in motor units that can already be activated, rather than by recruiting previously unavailable motor units.